Soil Freeze-Thaw and Water Transport Characteristics Under Different Vegetation Types in Seasonal Freeze-Thaw Areas of the Loess Plateau - Bo, Lanfeng; Li, Zhanbin; Li, Peng; Xu, Guoche; Xiao, Lie; Ma, Bo (Frontiers in Earth Science, 2021)
In the arid and semi-arid regions of the Loess Plateau, seasonal freezing and thawing influence soil water movement, and water movement directly influences vegetation growth. However, currently, research with regard to freezing and thawing processes under various vegetation types and the mechanism of soil water movement is lacking. Therefore, the present study explored soil water migration characteristics of two typical vegetation types (arbor land [AL] and shrub land [SL]) on the Loess Plateau during seasonal freezing and thawing processes using bare land (BL) as a control. We used field measured data for hourly soil temperature (ST) and soil water content (SWC) at a depth of 100 cm below the soil surface from November 2017 to March 2018. Freezing and thawing process was divided into three stages based on ST change (initial freezing period, stable freezing period, and thawing period). The results revealed that: 1) the maximum freezing depth of AL and SL was 60 cm, which was 30 cm less than that of BL. The freezing date of each soil layer in BL was the earliest and average ST value was the lowest. BL had the highest degree of freezing. The freezing of all soil layers in AL occurred at a later date than that of SL. ST and the minimum soil freezing temperatures were higher than those of SL, and the capacity of AL to resist freezing was higher; 2) the SWCs in AL and BL at depths of 0–10 cm and 10–30 cm decreased, whereas SWCs of AL and BL at a depth of 60 cm increased by 152% and 146%, respectively. The SWCs of SL at soil depths of 0–10 cm, 10–30 cm, and 30–60 cm increased by 46.3%, 78.4% and 205%, respectively. The amount and distribution of soil moisture in SL were optimum when compared to those of AL and BL. The results of the present study could provide a scientific basis for vegetation restoration in arid and semi-arid areas of the Loess Plateau.